Violence in affective-sexual relations between young people with a gender outline: from the speeches of young people from Piauí (Research, Society and Development, 2020)
The present study seeks to investigate the understanding of young Piaui people about health and sexuality issues, highlighting their understanding about the theme of dating violence. Adolescence and youth are stages of development predominantly marked by the search for identities and meanings, and it is also a period often characterized by multiple experiences, whether of relationships, sexual identifications, or even regarding gender, which externalize and clarify. However, sometimes this phase can be marked by adverse experiences, such as violence. The objective of the research is to analyze the perception that young people and adolescents have in relation to violence in sexual relationships / dating. This article is part of a larger research, and for the construction of this material, 6 interviews were selected from the 34 conducted with boys and girls between 14 and 24 years old about their knowledge about dating violence.